Evaluation of the Results of Polygraphy and Polysomnography Performed at Consecutive Times in the Detection of Obstructive Sleep Apnea: a Retrospective Analysis - İnci Şule Özer; Dilara Mermi Dibek; Cansu Ağırcan; İbrahim Öztura; Barış Baklan (Türk Uyku Tıbbı Dergisi)
Objective: Polysomnography (PSG) performed at a sleep center is the gold standard for diagnosing sleep apnea syndrome. When PSG cannot be performed due to late appointments or in pandemic conditions, the use of home devices such as polygraphs may be preferred. We aimed to investigate the adequacy and deficiencies of polygraphy (PG) in diagnosing obstructive sleep apnea syndrome in adults who underwent PSG and PG recording at our center. Materials and Methods: Patients who underwent cardiorespiratory PG and then PSG at the sleep center with suspicion of sleep apnea syndrome were retrospectively analyzed. Apnea Hypopnea Index (AHI) values were compared. There was a total of 34 patients in the study, 10 females and 24 males. Results: The mean AHI was 38.3±22.1 in PG and 43.5±27.5 in PSG. No statistically significant difference was found in AHI values between the two tests (p=0.065). In both groups, one (2.9%) patient had a normal AHI value. The AHI ratings of the patients on PLG were 4 (11.8%) mild, 8 (23.5%) moderate, and 21 (61.8%) severe, and on PSG, they were 5 (14.7%) mild, 6 (17.6%) moderate, and 22 (64.7%) severe. Conclusion: In our study, we found similar AHI values in PG used at home and PSG in the sleep center. When sleep apnea syndrome is suspected, if the PSG appointment in the sleep center is long, or the patient cannot sleep in the sleep center due to the occurrence of a pandemic or other reasons, a PG devices used at home may be preferred.